Minimal Nature in Walt Whitman’s Leaves of Grass (2024)
This paper offers an ecocritical interpretation of Walt Whitman’s renowned work, “Leaves of Grass.” The primary objective is to delve into the multifaceted interpretations of this text within the broader context of Whitman’s literary corpus. Our research is grounded in the premise that the act of writing is intricately interwoven with the natural world, particularly plant life. Consequently, we aim to scrutinize the various manifestations of plant imagery and symbolism present in Whitman’s oeuvre. The argument unfolds across three distinct sections: the first section delves into the influence of Ralph Waldo Emerson on Whitman’s thought; the second section investigates the portrayal of nature’s principles within “Leaves of Grass”; and finally, the third section critically examines the assumptions and implications of Whitman’s poetic approach to nature. Central to our thesis is the assertion that what we term “minimal natures” not only shape poetic construction and life itself but also engage with pertinent political issues.